EFFECT MODERATING OF SALESPERSONS ON CO-CREATION VALUE - Marlien, R.A; Rizal Rivai, Alimuddin; Soliha, Euis (Proceeding Fakultas Ekonomi, 2017)
The life insurance industry plays a role in mobilizing and increasing the accumulation of public funds, through savings and investment funds. Besides, it also regulates, allocates manage risk by maintaining the level of liquidity to face the uncertainty later on. The basic concept in this research is departed from the relationship between marketing and services marketing. The concept of collaboration is an extension of the above concept. This study aims to build collaboration as an antecedent of co-creation value. The capacity of salesperson is as a moderating variable in the relationship between customer participation and co-creation value. A set of hypotheses are built to analyze the effect of antecedents on co-creation values. The findings of this study found that customer participation and corporate values have no effect on the value of co-creation. The values of collaboration and salesperson's capabilities affect the value of co-creation, while the capability of the salesperson is not as a mediator instead of an independent variable.Keywords: Customer participation, Corporate Values, Collaboration Values, Co-Creation, Salesperson Capabilities